Modal Intelektual dan Nilai Perusahaan: Sebuah Tinjauan literatur sistematis - Malikah, Anik; Nandiroh, Umi (CV. AFDIFAL MAJU BERKAH, 2024)
This literature review examines the relationship between intellectual capital and corporate value. Intellectual capital is an intangible asset in an organization, including human capital, structural capital, and relational capital. This review aims to provide a comprehensive overview of existing empirical research, theories, and findings related to the impact of intellectual capital on company value. The study used a systematic strategy to identify relevant articles from academic databases and specialized journals. The selected studies are analyzed and synthesized to identify common themes and patterns. The findings show a positive relationship between intellectual capital and firm value, with research consistently showing that intellectual capital contributes to improved financial performance, market value, and competitive advantage. Various measurement and evaluation methods, such as scorecards, valuation techniques, and intellectual property management, have assessed the impact of intellectual capital. The review also highlights the importance of effective management and leveraging intellectual capital for long-term organizational success. However, the literature review identified several research gaps, including the need for more longitudinal studies, industry-specific investigations, and further exploration of how intellectual capital translates into corporate value. Overall, this review contributes to understanding how intellectual capital drives corporate value and provides insights for researchers, practitioners, and policymakers looking to leverage intangible assets for sustainable competitive advantage.